2012
DOI: 10.3389/fimmu.2012.00331
|View full text |Cite
|
Sign up to set email alerts
|

Novel Murine Dendritic Cell Lines: A Powerful Auxiliary Tool for Dendritic Cell Research

Abstract: Research in vitro facilitates discovery, screening, and pilot experiments, often preceding research in vivo. Several technical difficulties render Dendritic Cell (DC) research particularly challenging, including the low frequency of DC in vivo, thorough isolation requirements, and the vulnerability of DC ex vivo. Critically, there is not as yet a widely accepted human or murine DC line and in vitro systems of DC research are limited. In this study, we report the generation of new murine DC lines, named MutuDC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 51 publications
3
163
0
Order By: Relevance
“…We previously reported that our mouse CD8 + DC lines retained all major phenotypic and functional features of their in vivo counterparts, including characteristic cell-surface marker expression, responsiveness to TLR stimuli, patterns of cytokine and chemokine production, cross-presentation capacity, and T cell-stimulatory properties (33). This was further confirmed by studying the expression of 257 genes identified as cDCs, pDCs, CD8…”
Section: + Dcssupporting
confidence: 68%
See 1 more Smart Citation
“…We previously reported that our mouse CD8 + DC lines retained all major phenotypic and functional features of their in vivo counterparts, including characteristic cell-surface marker expression, responsiveness to TLR stimuli, patterns of cytokine and chemokine production, cross-presentation capacity, and T cell-stimulatory properties (33). This was further confirmed by studying the expression of 257 genes identified as cDCs, pDCs, CD8…”
Section: + Dcssupporting
confidence: 68%
“…Wild-type (WT) (MuTu1940), Tlr3 2/2 , and Ifnar1 2/2 CD8 + DC lines were established and cultured as described previously (33,34). Splenic CD8 + DCs were isolated from Flt3L-transgenic mice (35) or WT C57BL/6J mice using CD8 + DC purification kit (130-091-169; Miltenyi Biotec).…”
Section: Cellsmentioning
confidence: 99%
“…4H). Furthermore, ICG- 001 treatment of MutuDC1940 cells, a DC-derived cell line that has many characteristics of CD8α + DC(30), also resulted in strong downregulation of IRF8 (Fig. 4I).…”
Section: Resultsmentioning
confidence: 95%
“…The mutu-1940 DC cell line was used as the APC and alumina nanoparticles were used to facilitate intracellular delivery of isolated SLiPs31. Mutu-1940 DC was an established cell line from CD1c-SV40 large T antigen transgenic C57BL/6 mice32 and it was shown to closely resemble endogenous CD8 + conventional DCs (cDC). When CFSE labeled naïve OT-I T cells were stimulated by SLiPs-loaded mutu-1940 DCs, OVA-specific T-cell proliferation was observed when SLiPs was purified from B78H1-OVA but not B78H1-GFP tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…The B78H1 cell line is a MHC-I-deficient subclone of B16 melanoma; B78H1-D b , B78H1-K b , B78H1-D b K b stable cell lines were transfected with plasmids expressing MHC-Ia molecules, these B78H1 cell lines and CT26 were kindly provided by Hyam I. Levitsky (Johns Hopkins University, Baltimore, MD); B78H1-R-OVA-GFP and B78H1-GFP stable cell lines were transfected with plasmids expressing short-lived GFP-R-OVA fusion protein or GFP alone16. Mutu-1940 DCs from C57BL/6 mice were kindly provided by Dr. Hans Acha-Orbea (University of Lausanne, Epalinges, Switzerland)32. Listeria mono cytogenes that express the endogenous 4T1 tumor antigen AH1 (Delta-actA-Lm-AH1-A5) were kindly provided by Dr. Keith Bahjat (Earle A. Chiles Research Institute, Portland, OR).…”
Section: Methodsmentioning
confidence: 99%